#### Answer

$81$

#### Work Step by Step

$a^m \cdot a^n = a^{m+n}$
Use the rule above to obtain:
$=3^{x+(2-x)+2}
\\=3^{(x-x+2+2)}
\\=3^{0+4}
\\=3^4
\\=3(3)(3)(3)
\\=81$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

$81$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.